The Impact of Tribal Ethnocentrism on National Identity in Libyan Society: A Sociological Analytical Study - Abdulhakim Almukhtar Mohammed (Journal of Scientific and Human Dimensions, 2026)
This study explores the impact of tribal ethnocentrism on national identity within the context of contemporary Libyan society. The research addresses the problem of rising tribal and regional loyalties at the expense of a unified national identity, particularly following the collapse of state institutions and the resulting political and security vacuum. By employing a sociological analytical approach, the study examines the root causes of tribal fanaticism—including inherited traditions, cultural factors, and political exploitation —and evaluates how these factors weaken social cohesion and state-building efforts. The findings indicate that while tribes historically served as social regulators, their transformation into political tools has deepened social fragmentation and threatened civil peace. The paper concludes with recommendations to strengthen national identity through educational curricula, equitable resource distribution, and the establishment of a robust legal framework that transcends sub-national allegiances.
Keywords: Tribal Ethnocentrism; National Identity; Libyan Society; Social Cohesion; Political Stability